Molecular analysis and favorable clinical outcomes in real-world patients with metastatic renal cell carcinoma. (3rd October 2022) - Donskov, Frede; Pinto, Cathy Anne; Predoiu, Raluca; Fox, Claire; Georgsen, Jeanette Baehr; Skaarup, Katrine; Burcu, Mehmet; Perini, Rodolfo; Steiniche, Torben
Abstract: Background: Prior biomarker studies have mainly been restricted to advanced RCC patients treated in clinical trials or have had limited integration of immunotherapy features such as programmed death ligand (PD-L)-1 with gene expression signatures intended to capture other canonical pathways to confirm their prognostic value. Material and methods: PD-L1 and PD-L2 by immunohistochemistry (IHC), PD-L2 messenger RNA (mRNA), and 10 gene expression profile (GEP) signatures targeting immune, angiogenesis and canonical pathways were analyzed in nephrectomy specimens from 227 advanced clear cell RCC (ccRCC) and 42 non-clear cell RCC (nccRCC) patients treated with targeted therapies including VEGF and mTOR inhibitors. Biomarker association with best overall response (BOR), progression-free survival (PFS), and overall survival (OS) were evaluated using multivariable modeling. Except for PD-L1 IHC and angiogenesis, tested with a nominal p -value of .05, multiplicity control was applied with a 0.1 significance level given limited experience in this setting. Results: The strongest biomarker correlations were observed for hypoxia inducible factor (HIF)-2a and angiogenesis signatures (rho = 0.860 [ccRCC], 0.819 [nccRCC]); hypoxia and glycolysis signatures (rho = 0.943 [ccRCC], 0.973 [nccRCC]); PD-L2 mRNA and T-cell-inflamed GEP signatures (rho = 0.764 [ccRCC], 0.897 [nccRCC]); and PD-L2 mRNA and monocytic myeloid-derived suppressor cell signature (rho = 0.787 [ccRCC], 0.815 [nccRCC]). For ccRCC, higher angiogenesis expression was associated with improved BOR (OR:2.85 [95%CI:1.37, 5.93]), longer PFS (HR:0.61 [95%CI:0.45, 0.82]) and OS (HR:0.74 [95%CI:0.54, 1.00]); higher PD-L1 expression with shorter OS (HR:1.44 [95%CI:1.01, 2.07]). For nccRCC, there was more than a two-fold increased risk with longer OS associated with lower angiogenesis (HR:2.43 [95%CI:1.04, 5.68]), glycolysis (HR:7.03 [95%CI:1.51, 32.76]) and hypoxia (HR:8.83 [95%CI:1.69, 46.05]) gene signature expression. Conclusion: Data pointed at PD-L1 IHC and angiogenesis expression in ccRCC and hypoxia, glycolysis, and angiogenesis expression in nccRCC as potential prognostic factors. These findings may have implications for the design and interpretation of advanced RCC trials and to identify potential targets for combination therapy strategies.